The Impact of Transparency, Resources, Good Governance and Professionalism on Successful Operations of Destination Management Companies (DMCs) (Global Journal of Management and Business Research, 2025)
Abstract not found
Keywords: good governance; professionalism; resource managment; transparency; operational success; Sri Lanka; sustainable tourism